Simulating Sustainable Color-Form Decisions in AI-Driven Eco-Brand Identity Design - Elena, Sofia; Alexander, Liam (University of Science and Computer Technology, 2026)
Integrating sustainability into brand identity design remains challenging, as the harmony between visual aesthetics, primarily color and shape, and eco-branding values often relies on subjective judgment, highlighting a lack of data-driven approaches. While AI-assisted design tools have demonstrated utility, their primary focus remains on aesthetic generation rather than sustainable design optimization. This research addresses this gap by proposing a simulation-based framework that, through simulation and expert review, examines and evaluates how AI-assisted color-form choices influence both aesthetic consistency and ecological brand alignment. Using synthetic data and scenario modeling, we created a simulation that analyzes color and form parameters against sustainability indicators across three scenarios: Aesthetic-only, Sustainability-only, and an Integrated Eco-Aesthetic approach. Eco-Alignment was computed using cosine similarity of semantic embeddings across 50 simulation runs for each scenario, providing a quantifiable measure of semantic consistency with eco-brand values. The results indicate that the integrated approach outperformed single-focus scenarios in balancing aesthetic harmony and eco-alignment. At the same time, the Color-Form Sustainability Matrix identified specific combinations, such as earthy tones paired with organic shapes, that achieved the highest Eco-Alignment Scores. This study contributes methodologically by linking computational aesthetics with sustainable design through structured simulation, offering designers an evidence-informed framework for making visual decisions that support environmental ethos and reduce resource-intensive trial-and-error design processes.